Can Patient Navigation Improve Receipt of Recommended Breast Cancer Care? Evidence From the National Patient Navigation Research Program - Ko, Naomi Y. (American Society of Clinical Oncology, 2014)
PURPOSE: Poor and underserved women face barriers in receiving timely and appropriate breast cancer care. Patient navigators help individuals overcome these barriers, but little is known about whether patient navigation improves quality of care. The purpose of this study is to examine whether navigated women with breast cancer are more likely to receive recommended standard breast cancer care. PATIENTS AND METHODS: Women with breast cancer who participated in the national Patient Navigation Research Program were examined to determine whether the care they received included the following: initiation of antiestrogen therapy in patients with hormone receptor–positive breast cancer; initiation of postlumpectomy radiation therapy; and initiation of chemotherapy in women younger than age 70 years with triple-negative tumors more than 1 cm. This is a secondary analysis of a multicenter quasi-experimental study funded by the National Cancer Institute to evaluate patient navigation. Multiple logistic regression was performed to compare differences in receipt of care between navigated and non-navigated participants. RESULTS: Among participants eligible for antiestrogen therapy, navigated participants (n = 380) had a statistically significant higher likelihood of receiving antiestrogen therapy compared with non-navigated controls (n = 381; odds ratio [OR], 1.73; P = .004) in a multivariable analysis. Among the participants eligible for radiation therapy after lumpectomy, navigated participants (n = 255) were no more likely to receive radiation (OR, 1.42; P = .22) than control participants (n = 297). CONCLUSION: We demonstrate that navigated participants were more likely than non-navigated participants to receive antiestrogen therapy. Future studies are required to determine the full impact patient navigation may have on ensuring that vulnerable populations receive quality care.